Between Idea and Reality - Radosław Zdaniewicz (Fasciculi Archaeologiae Historicae)
The considerations based on the artefacts discovered during the excavations of the motte tower in Widów are an interesting source for research on the chivalric culture of the Middle Ages. Unfortunately, it is extremely difficult to connect the discovered sword fragment – regarded as a symbol of knighthood – with a specific representative of the Widowski family. Leaving aside any purely theoretical deliberations on the circumstances in which this artefact was buried among the remains of the building with other objects used in the manor house, it must be admitted that this discovery can hardly be considered accidental and completely unrelated to the occupants of the said residence. It is certainly very likely that the analysed artefact is material evidence of the cohabitation of the manor’s inhabitants with a sword, an attribute of the knightly class and a symbol of their membership in the group of local milites. Finds of stove tiles with various images associated with chivalric culture are testimony to the fact that the local manor belonged to people whose material status, but also spiritual needs and worldview went beyond the everyday mundane life of the local country estate owners. The traces of material culture uncovered through archaeological research are carriers of ideas that complete the picture of a past reality.